Advanced ceramics: Evaluation of the mechanism of stock removal and ground surface quality - Bianchi, Eduardo Carlos [UNESP]; Da Silva, Eraldo Jannone [UNESP]; Neto, Luiz Daré [UNESP]; Da Silva Júnior, Carlos Elias [UNESP] (SAE International, 1999)
The aim of this work is to evaluate the mechanism of stock removal and the ground surface quality of advanced ceramics grounded by a plane tangential grinding process with diamond grinding wheels. The analysis of the grinding performance was done regarding the cutting surface wear behavior of the grinding wheel for ceramic workpieces. The discussion about the results emphasized the wear mechanism of the grinding wheel cutting surface and the cutting phenomenology of the grinding process. The grounded surface was evaluated using Scanning Electron Microscopy (SEM). © 1999 Society of Automotive Engineers, Inc.
Keywords: A-plane; Advanced Ceramics; Grinding performance; Grinding process; Grounded surfaces; Stock removal; Surface wear; Wear mechanisms; Work pieces; Grinding (machining); Grinding wheels; Scanning electron microscopy; Surface properties; Tribology; Ceramic materials